COLIGENTA treatment of small intestinal bacterial overgrowth. Results of an open study. Issue 1 (January 2021) - Bouchoucha, Michel; Fysekidis, Marinos; Lekhal, Céline; Bejou, Bakhtiar Daniel; Sabate, Jean-Marc; Benamouzig, Robert
Abstract: Purpose: The treatment of small intestinal overgrowth (SIBO) varies according to the center. The present study aimed to evaluate the efficacy of COLIGENTA, an association of colimycin and gentamycin, on SIBO symptomatology and breath test normalization Patients and Methods: In this prospective cross-sectional open study, 150 patients with functional bowel disorders and SIBO diagnosed by lactulose hydrogen breath test (LHBT) underwent COLIGENTA oral treatment. A new HLBT was performed 4 weeks after the first HLBT. Results: The patients were mainly female (74%), with a mean age of 47.4 ± 16.2 years and a body mass index of 26.2 ± 5.9 kg/m². After treatment, a decrease of expired hydrogen concentration ( P <0.001) was found in the entire population. Improvement of gastrointestinal symptoms was found in 129 patients (86%), while the breath test's normalization was found in 62 patients (42%). Logistic regression showed that normalization of bowel symptoms was not associated with demographics, clinical, or hydrogen breath concentration. In contrast, normalization of LHBT was associated with an increase of breath hydrogen concentration at time 100 min during the first test ( P = 0.003; OR=1.072; 95%CI= [1.023–1.123]). Conclusion: The present study shows that 10-days of COLIGENTA treatment has a high SIBO clinical improvement rate and can be used as the first or second treatment line.